PENERAPAN PENURUNAN NILAI INSTRUMEN KEUANGAN BERDASARKAN PSAK 50 DAN 55 (REVISI 2006) DAN PERUBAHAN YANG HARUS DILAKUKAN PERUSAHAAN - Rizka Annisa (Bina Ekonomi, 2011)
Convergence between US GAAP and IFRS certainly affect to accounting standard that occur now in Indonesia.  Indonesia is harmonizing with  IFRS and  revising  several  standards  so that  it will comply with  International Standard. One of the standard that being revised is PSAK 50 (Presentation and Disclosure of Financial Instrument) and PSAK 55 (Recognition and Measurement of Financial Instrument). Along with harmonization and applying fair value accounting, financial instrument need  to be assessed  to their market  value if there  is descent of the value,  the financial  instrument need to be  impaired. With applying PSAK 50 and 55 (revision 2006), the impairment process should be supported by reliable, documented data, and need another data to prove that the value of financial instrument is descent. Company has to prepare themself to face the changes that happened, which is changes in information system, organization, technology and human resource.  In addition, company should understand overall of PSAK 50 and PSAK 55, because there is a lot of detailed rules in this revision.